Influence of therapy chronic heart failure of functional class III on regulatory adaptive status - E. S. Rokotyanskaya (Кубанский научный медицинский вестник, 2014)
100 patients with CHF FC III against the background of ischemic heart disease (IHD) and/or stage III hypertensive disease (HD). All them administered of complex therapy (Quinapril, Torasemide, Spironolactone). Upon randomization, Group 1 consisted of 56 patients (57,5±21,7 years old) and received metoprolol succinate of sustained release (Betalok ZOK, Sweden's AstraZeneca, 59,1±12,7 mg per day). Group 2 consisted of 44 patients (57,1±21,4 years old) and received Ivabradine, inhibitor of If channels in the sinoatrial node (Coraxan, France's Servier, 12,1±4,6 mg per day) in cases when use of beta-blockers (BB) was not possible. VO2max treadmill tests, echocardiography, 24-hour blood pressure monitoring, NT-proBNP blood plasma test were done initially and 6 months in. A cardiorespiratory synchronism test was done in order to objectively evaluate the regulatory adaptive status (RAS). On the result of reseache, complex therapy with the use of Ivabradine showed comparable clinical effects with metoprolol succinate: improved the structural and functional condition of the myocard, increased tolerance to physical exercise, caused reduction in the level of NT-proBNP in blood plasma and increase of VO2мах during physical strain, but more than BB positively influenced the RAS. Therefore, Ivabradine can serve as an alternative to BB if it's impossible to use in patients with CHF FC III against the background of IHD and/or stage III HD.